2023
DOI: 10.1029/2022jd037616
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Cycle and Dipolar Pattern of Precipitation Over Borneo During the MJO: Linear Theory and Nonlinear Sensitivity Experiments

Abstract: The precipitation anomaly over Borneo features a dipolar pattern under the influence of the Madden‐Julian Oscillation (MJO). To understand the formation mechanisms of this pattern, a linear theory is developed to study the factors controlling its diurnal cycles and the dipolar pattern. The theory predicts that the prevailing wind is primarily responsible for the asymmetry over an idealized island, while the topography plays a critical role in the leeward convergence and convection asymmetry. The results are la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…First, the number of stations for bias correction was not distributed evenly throughout the study site. This may disregard the influence of sea breeze on rainfall formation (Zhou et al, 2023) and temperature especially in the southern part. During dry season strong winds often occur, which trigger high land temperatures (Usup and Hayasaka, 2023), that is not captured by the available weather stations.…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of stations for bias correction was not distributed evenly throughout the study site. This may disregard the influence of sea breeze on rainfall formation (Zhou et al, 2023) and temperature especially in the southern part. During dry season strong winds often occur, which trigger high land temperatures (Usup and Hayasaka, 2023), that is not captured by the available weather stations.…”
Section: Discussionmentioning
confidence: 99%
“…High‐resolution model simulations, incorporating the analysis of vertical shear components, would be the most effective approach to address the complexities of the studied phenomena. Given the significant impact of topography on offshore propagation rainfall (Zhou et al., 2023), it would be intriguing to investigate the influence of topography in offshore LLJs through sensitivity experiments. The findings in the present study deepen our understanding of the complex dynamics of the southwesterly monsoon LLJ and provide a basis for future research on the regional monsoon system.…”
Section: Discussionmentioning
confidence: 99%
“…During the summer, the dominant winds along the eastern coast of China are southeast winds, which have a significant impact on the coastal climate. When studying the land-sea breeze variations, we exclude the background large-scale systems such as the East Asian monsoon for the sake of convenience, while acknowledging that the land/sea breeze is also influenced by prevailing wind associated with large-scale systems (e.g., see Zhou et al 2022Zhou et al , 2023. The range of selected breeze directions also varies according to the coastline orientation.…”
Section: Windmentioning
confidence: 99%
“…The different dominant rainfall factors between offshore and coastal areas lead to the difference in the characteristics of land and sea precipitation. Zhou et al (2022Zhou et al ( , 2023 indicated that either thermally or mechanically forced mesoscale local circulation can interact with convection, shaping the spatial pattern and diurnal variations of the precipitation around the tropical island. Du and Rotunno (2018) focused on the diurnal precipitation and wind characteristics manuscript submitted to Climate Dynamics on the Guangdong coast, and showed the diverse onshore and offshore propagation patterns of the diurnal precipitation.…”
Section: Introductionmentioning
confidence: 99%